Focus Loss While Driving Detection by Using Prior Stage ERP as Baseline - Aminuddin, M.M.M; Nasir, H.M. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
Driving demands a full focus on the road to avoid any kind of unfortunate events. However, it is common to loss focus over time especially on the road with less traffic and long journey. Studies have shown that quiet number of accidents happened due to loss of focus. Hence, this on-going study is to develop a device to detect focus loss while driving. In our preliminary papers, we have shown that loss of focus is associated to the declining of evoked response potential (erp) amplitude over time. However, to determine the significant decline of amplitude is challenging due to inter-variability of individuals. Hence, in this paper, we propose novelty detection approach by using prior stage of recording as baseline to extract focus loss in single trials of erp of respective individuals. Erps of 20 subjects were recorded while driving a simulator car. The obtained results suggest that the proposed approach detects the attention loss successfully but with a delay as few seconds are needed to obtain the baseline. Novelty detection by using prior stage of recording as baseline is promising but improvement need to be done to apply it in real time.